PENGEMBANGAN LKPD BERBASIS CHEMO-EDUTAINMENT (CET) PADA MATERI STOIKIOMETRI - Rani Puspita Hami (UIN AR-RANIRY, 2021)
The objective of this study was to create learning media in the form of Chemo-Edutainment-based worksheets on stoichiometric material and to determine the characteristics and quality of the products being developed. It used a research and development model with a 4-dimensional development model which consisted of define, design, develop, and disseminate. However, research activities are only carried out until the development stage considering the limited time for research and the unfavorable conditions of the Covid-19 pandemic. The product characteristics developed are arranged based on the CET components. The quality of CET-based student worksheets on stoichiometric material is categorized as very feasible with a coefficient (V) of 0.86 for each expert validation. The results of student responses to the CET-based student worksheets showed an average percentage of 82% with a sufficiently valid category to be used as a reference for learning resources. To measure students’ cognitive skill, it used pretest and posttest throughout the N-gain test. Then, the N-gain value of 0.83 is classified as a high category.